Antioxidant, antimicrobial and tyrosinase inhibitory activities of xanthones isolated from artocarpus obtusus F.M. Jarrett - Abd Manaf, Ali; Najihah, Mohd. Hashim; Mawardi, Rahmani; Gwendoline, Cheng Lian Ee (2012)
: One of the most promising plants in biological screening test results of thirteen Artocarpus species was Artocarpus obtusus FM Jarrett and detailed phytochemical investigation of powdered dried bark of the plant has led to the isolation and identification of three xanthones; pyranocycloartobiloxanthone A (1), dihydroartoindonesianin C (2) and pyranocycloartobiloxanthone B (3). These compounds were screened for antioxidant, antimicrobial and tyrosinase inhibitory activities. Pyranocycloartobiloxanthone A (1) exhibited a strong free radical scavenger towards DPPH free radicals with IC50 value of 2 µg/mL with prominent discoloration observed in comparison with standard ascorbic acid, α-tocopherol and quercetin, The compound also exhibited antibacterial activity against methicillin resistant Staphylococcus aureus (ATCC3359) and Bacillus subtilis (clinically isolated) with inhibition zone of 20 and 12 mm, respectively. However the other two xanthones were found to be inactive. For the tyrosinase inhibitory activity, again compound (1) displayed strong activity comparable with the standard kojic acid